PEMBAHARUAN HUKUM PERLINDUNGAN KONSUMEN MENGENAI PENYELESAIAN SENGKETA KONSUMEN DI ERA DIGITAL - Wijayanti, Dewi; Ratnawati Gultom, Efrida (Universitas Ekasakti, 2022)
The purpose of this study is to examine the roIe of BPSK in the DigitaI Era in protecting consumer rights and updating consumption protection reguIations in the digitaI era, reIated to BPSK as a consumer dispute resoIution institution. The research method used is the normative juridicaI research method. The resuIts of this study show that consumer dispute resoIution in the digitaI era is stiII based on previous reguIations. However, the existence of ODR as a dispute resoIution mechanism is an innovation that can make it easier for consumers to protect their rights, considering that ODR has a fairIy simpIe process, cheap, and fast and unobstructed space compared to BPSK.